2018
DOI: 10.3389/fcimb.2018.00185
|View full text |Cite
|
Sign up to set email alerts
|

Iron at the Centre of Candida albicans Interactions

Abstract: Iron is an absolute requirement for both the host and most pathogens alike and is needed for normal cellular growth. The acquisition of iron by biological systems is regulated to circumvent toxicity of iron overload, as well as the growth deficits imposed by iron deficiency. In addition, hosts, such as humans, need to limit the availability of iron to pathogens. However, opportunistic pathogens such as Candida albicans are able to adapt to extremes of iron availability, such as the iron replete environment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 185 publications
(239 reference statements)
0
55
0
1
Order By: Relevance
“…[ 5 12 13 ] Recent studies have shown that iron is at the center of interaction for C.albicans and ferritin plays a key role in it. [ 14 ] C. albicans has shown multiple approaches to acquire iron from the host and ferritin has promoted the process. [ 15 ] Children with high C. albicans count have five times higher chance to develop ECC compared to those without C. albicans ,[ 16 ] suggesting potent cariogenic characteristics, which lead to the development and progression of S-ECC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 12 13 ] Recent studies have shown that iron is at the center of interaction for C.albicans and ferritin plays a key role in it. [ 14 ] C. albicans has shown multiple approaches to acquire iron from the host and ferritin has promoted the process. [ 15 ] Children with high C. albicans count have five times higher chance to develop ECC compared to those without C. albicans ,[ 16 ] suggesting potent cariogenic characteristics, which lead to the development and progression of S-ECC.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the ability of a fungal pathogen to sequester iron from different host iron-containing proteins for growth and proliferation is a key virulence determinant [81]. It has been thoroughly demonstrated that C. albicans has a mechanism to obtain iron from haem and haemoglobin that is independent of both the reductive and non-reductive systems, i.e., xenosiderophore transport [82,83]. The ability to utilise haem/haemoglobin depends on the conserved family of common in several fungal extracellular membrane proteins or CFEM proteins, which has an eight cysteine-containing domain: Rbt5, Rbt51/Pga10, Pga7, and the secreted haemophore, Csa2 [81,[84][85][86][87][88][89].…”
Section: Haem and Haemoglobin Utilisationmentioning
confidence: 99%
“…xenosiderophores (e.g., ferricrocin), extensively reviewed in studies by Fourie, Kuloyo, Mochochoko, Albertyn, and Pohl (2018) and Gerwien et al (2018). The already mentioned invasin Als3, required for induced endocytosis, is also crucial for acquiring iron from ferritin, which is the main iron storage protein in oral epithelial cells (Almeida et al, 2008).…”
Section: Pick-pocketing -Fungi Collect Metals From the Host Environmentioning
confidence: 99%